The zebrafish common cardinal veins develop by a novel mechanism: Lumen ensheathment - Helker, Christian S. M.; Schuermann, Annika; Karpanen, Terhi; Zeuschner, Dagmar; Belting, Heinz-Georg; Affolter, Markus; Schulte-Merker, Stefan; Herzog, Wiebke (Development, 2013)
The formation and lumenization of blood vessels has been studied in some detail, but there is little understanding of the morphogenetic mechanisms by which endothelial cells (ECs) forming large caliber vessels aggregate, align themselves and finally form a lumen that can support blood flow. Here, we focus on the development of the zebrafish common cardinal veins (CCVs), which collect all the blood from the embryo and transport it back to the heart. We show that the angioblasts that eventually form the definitive CCVs become specified as a separate population distinct from the angioblasts that form the lateral dorsal aortae. The subsequent development of the CCVs represents a novel mechanism of vessel formation, during which the ECs delaminate and align along the inner surface of an existing luminal space. Thereby, the CCVs are initially established as open-ended endothelial tubes, which extend as single EC sheets along the flow routes of the circulating blood and eventually enclose the entire lumen in a process that we term 'lumen ensheathment'. Furthermore, we found that the initial delamination of the ECs as well as the directional migration within the EC sheet depend on Cadherin 5 function. By contrast, EC proliferation within the growing CCV is controlled by Vascular endothelial growth factor C, which is provided by circulating erythrocytes. Our findings not only identify a novel mechanism of vascular lumen formation, but also suggest a new form of developmental crosstalk between hematopoietic and endothelial cell lineages. © 2013.
CRIS-Team Scopus Importer:2020-09-23
Keywords: Angioblast specification; Cadherin 5; Collective migration; Common cardinal vein; Lumen formation; Vegfc